Parkinsonism in PGK1 deficiency implicates the glycolytic pathway in nigrostriatal dysfunction. (July 2019) - Morales-Briceño, Hugo; Ha, Ainhi D.; London, Kevin; Farlow, David; Chang, Florence C.F.; Fung, Victor S.C.
Abstract: Background: Phosphoglycerate kinase-1 deficiency is caused by X-linked recessive mutations in PGK-1 and associated with haemolytic anaemia, rhabdomyolysis, myopathy and nervous system involvement. Some cases have been rarely associated with juvenile Parkinsonism however the causal relationship between PGK1 deficiency and nigrostriatal dysfunction causing Parkinsonism has not been determined. Objective and methods: To investigate the nigrostriatal system using 99mTc-TRODAT-1 SPECT binding and report the phenotype of three affected males with early onset levodopa responsive Parkinsonism harbouring the c.491 A > T/p.D164V pathogenic variant. Results: All patients initially presented with infantile-onset encephalopathic and stroke-like episodes, haemolytic anaemia and epilepsy. Two patients had an early-onset and one juvenile-onset levodopa responsive Parkinsonism with motor fluctuations. 99mTc-TRODAT-1 SPECT showed severe bilateral reduced putaminal uptake in the three patients. None of the patients had structural lesions that could explain either pre- or postsynaptic dopaminergic dysfunction. Conclusion: These cases provide strong evidence of a causal relationship between PGK1 deficiency and nigrostriatal pathology causing Parkinsonism. These findings have potential implications for our understanding of the pathophysiology of nigrostriatal degeneration in sporadic PD. Highlights: PGK1 deficiency is a differential diagnosis of juvenile or early onset Parkinsonism. Parkinsonism combined with hemolytic anemia, myopathy, epilepsy and intellectual disability are clues for the disorder. The Parkinsonism in PGK1 deficiency is associated with severe reduction of putaminal Tc-99m TRODAT SPECT binding. Parkinsonism in patients with PGK1 deficiency suggest that reduced glycolysis may contribute to nigrostriatal damage.